Subjective well-being, disability and adaptation - Fafchamps, M; Kebede, B (CSAE (University of Oxford), 2008)
In many developing countries poor infrastructure – including sanitation and health facilities – exposes the population to high risks of disability. Low standards of health and safety at work and at home, coupled with political, ethnic, and domestic violence, also contribute to raising the risk of becoming physically disabled. The effect of physical disability on people’s lives is likely to be worse than in developed economies because of the reliance on physical labour for income generation – for example, in farming. Higher levels of national income and technological capability may also enable societies to make the investments required to enable disabled individuals to be productively employed. Finally, since formal social insurance is usually lacking in developing countries, the effect of disability on welfare is expected to be higher as disabled people must rely on social networks that have limited capacity to pool risks.